Diseño de un plan estratégico basado en el uso de redes sociales para el medio de comunicación televisivo tv color en la ciudad de Latacunga periodo 2013-2014 - Zapata Vinueza, Edwin Mauricio (2015)
This research work was done in TV Color television media from Cotopaxi province, it claims to improve the strategies of this media has to reach to its audience. The application of research methods as: observation and the application of surveys involving local television viewers who like TV color media, were taken into consideration, this process allows to get important information about how this media performs in communication. This proposal has as main objective to implement a new strategy based on the social platforms use which will allow to the TV color and viewers interact in a fast way moreover, it will help to the interlocutors to be an active part of the media through the interaction in the social networks.